Powerful learning : what we know about teaching for understanding - Darling-Hammond, Linda, 1951-; Barron, Brigid; Pearson, P. David; Schoenfeld, Alan H.; Zimmerman, Timothy D.; Cervetti, Gina N.; Tilson, Jennifer L. (San Francisco, CA : Jossey-Bass, 2008)
The nation's leading education experts present the best teaching strategies for powerful learning Teaching: what works, what doesn't, and why? Within the fields of reading, math, and science, bestselling author Linda Darling-Hammond and colleagues describe, in clear and practical terms, the best teaching methods for K-12 student understanding. Rich classroom stories show that students designing and working together on engaging projects are challenged to do more than just memorize facts. This invaluable resource offers innovative strategies to support student learning. Linda Darling-Hammond (Stanford, CA) is the Charles E. Ducommun Professor of Education at Stanford University. The George Lucas Educational Foundation (GLEF) is a nonprofit foundation that gathers and disseminates information on K-12 teaching and learning in the Digital Age
Includes bibliographical references and indexes.
Keywords: Learning; Effective teaching -- United States